2016
DOI: 10.14238/pi56.1.2016.48-56
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors at birth for stunting at 24 months of age in rural Indonesia

Abstract: Background The problems of stunting are its high prevalence as well as the complexity of its risk factors. Identifying the modifiable prognostic factors at birth may reduce the shortterm as well as longterm effects of stunting in later life.Objective To estimate the influence of prognostic factors detected at birth for stunting at 24 months of age and the occurence of reversal of stunting at 24 months of age among children in a rural area of Indonesia.Methods Subjects (n=343) were born to mothers participating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
2
7
0
3
Order By: Relevance
“…We also found substantial evidence that boys were at a much greater risk of stunting than girls in Indonesia, including one longitudinal RCT, but sex-based biology is not in the WHO framework (Julia, van Weissenbruch, Delemarre-van de Waal, & Surjono, 2004;Prawirohartono et al, 2016;Rachmi et al, 2016b;Ramli et al, 2009;Sandjaja et al, 2013;Sari et al, 2010;Semba, de Pee, Hess, et al, 2008;Semba et al, 2011;Torlesse et al, 2016). Although boys are generally more susceptible to stunting than girls in developing countries, the mechanism for this is poorly understood (Bork & Diallo, 2017).…”
Section: Community and Societal Factorsmentioning
confidence: 81%
See 1 more Smart Citation
“…We also found substantial evidence that boys were at a much greater risk of stunting than girls in Indonesia, including one longitudinal RCT, but sex-based biology is not in the WHO framework (Julia, van Weissenbruch, Delemarre-van de Waal, & Surjono, 2004;Prawirohartono et al, 2016;Rachmi et al, 2016b;Ramli et al, 2009;Sandjaja et al, 2013;Sari et al, 2010;Semba, de Pee, Hess, et al, 2008;Semba et al, 2011;Torlesse et al, 2016). Although boys are generally more susceptible to stunting than girls in developing countries, the mechanism for this is poorly understood (Bork & Diallo, 2017).…”
Section: Community and Societal Factorsmentioning
confidence: 81%
“…IUGR and preterm birth have been strongly associated with child stunting in Indonesia. In a secondary analysis of data collected between 1995 and 1999 in an RCT in rural Indonesia, premature birth was associated with an RR of 7.11 (95% CI [2.07, 24.48]) of stunting in children 24 months (Prawirohartono, Nurdiati, & Hakimi, ). Rachmi et al () found that children 24–59 months were less likely to be stunted if at birth they weighed between 2.5 and 3.9 kg (AOR 0.62, 95% CI [0.39, 0.98]) or ≥4 kg (AOR 0.49, 95% CI [0.28, 0.87]), compared with children <2.5 kg in the IFLS.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the risk factors for stunting remain inconclusive. 13 A previous study reported that severe household food insecurity and lower socio-economic status were significant contributors to stunting incidence in Southeastern Kenya. 14 In addition, another study in Nepal showed that low family income and prolonged breastfeeding for more than 12 months were significant risk factors for stunting.…”
mentioning
confidence: 97%
“…Dampak buruk stunting sudah diketahui oleh banyak orang, namun patofisiologi stunting masih kurang dipahami. Nutrisi (Nailis et al, 2017;Sari et al, 2016), berat badan lahir rendah, jenis kelamin, kelahiran prematur (Aryastami et al, 2017;Cruz-Cruz et al, 2018;Prawirohartono et al, 2016), infeksi dan sanitasi (Aridiyah et al, 2015;Torlesse et al, 2016). Penelitian lain juga menunjukkan bahwa pemberian ASI Eksklusif, makanan pendamping ASI dan defisiensi mikronutrien memainkan peran penting pada kejadian stunting.…”
Section: Pendahuluanunclassified